Kualitas Fisik Bakso Daging yang Diiradiasi dengan Sinar Gamma pada Penyimpanan Suhu Ruang - Deudeu Lasmawati; Henny Widyastuti; Ashri Mukti Benita; Rindy Panca Tanhindarto; Farah Nurlidar; Indra Mustika Pratama (LPPM Universitas Terbuka, 2021)
This study was aimed to investigate the meatballs physical qualities that are irradiated with high-doses of gamma rays. This study used the irradiation method with the dosage of 20, 25and 35 kGy and storage at room temperature. For the control (0 kGy), storage was done in the freezer. The results showed that at 0 month, the samples water contents at 20; 25; 35 kGy were 67,03%; 67,50%; 66,67%, with significant difference (p<0.05) to control 68,73%. Water content (%) at 2 months were 65,03%; 66.00%; 67.50% and control 63,23% 2 months hassignificant difference (p<0.05) but still meet the SNI standard (<70%). Optimum water activity was obtained at irradiation dose of 35 kGy. The pH results doses of 20; 25; 35 kGyfor 0 month were 6,35; 6,34; 6,39 and 2 months were 6,59; 6,47; 6,46, respectively. pH of control was 5,87 at 0 month and 6,49 at 2 months. The pH of samples stored for 0 month wererelatively higher than the control pH. At 2-month storage, the pH of the samples was lower than the control, but still meets the standard. Meatball irradiation up to 35 kGy can be used as an alternative for preservation at room temperature.